Differential expression of circular RNAs in bone marrow‐derived exosomes from essential thrombocythemia patients. (31st December 2020) - Wang, Qiang; Yu, Guopan; He, Han; Zheng, Zhongxin; Li, Xuan; Lin, Ren; Xu, Dan
Abstract: Circular RNAs (circRNA) are closely associated with the pathogenesis of various hematological diseases. However, little is known about the potential functions of circRNAs in essential thrombocythemia (ET) development. The circRNA profile alterations in the bone marrow of ET patients were mainly investigated in this study. The sizes of exosomes derived from human bone marrow tissues were validated by the nanoparticle tracking analysis (NTA) method. CD63 and TSG101 expressions in exosomes were analyzed by western blot analysis. The profiles and differential expression of circRNAs in bone‐derived exosomes were characterized by high‐throughput sequencing. Herein, circular structures and expression of circRNAs were verified by Sanger sequencing and real‐time polymerase chain reaction, respectively. The circRNA‐miRNA‐mRNA networks were predicted using the Cytoscape software. And we detected the effect of circ_0014614 on the transformation of K562 cells into megakaryocytes. Exosomes derived from the bone marrow of ET patients and healthy volunteers showed a diameter between 70 and 140 nm and expressed high CD63 and TSG101. Meanwhile, the circRNA profiles were significantly altered in bone marrow–derived exosomes from ET patients, among which circDAP3, circASXL1, and circRUNX1 were significantly downregulated in ET patients, thus conferring a new insight into the role of circRNAs in the pathogenesis of ET. Besides this, circRNA‐encoding genes and miRNA‐mRNA networks targeted by this three circRNA were involved in various biological processes and signaling pathways. And circ_0014614 could inhibit K562 cells' differentiation into megakaryocytes. The predictions of the potential function of these three differentially expressed circRNAs along with their interaction with specific miRNAs could provide a basis for circRNA‐based ET diagnosis and treatment.